A qualitative assessment of the effects of interactive design elements on the perceived learning outcome of musical skills with a computer-assisted musical instrument tutoring system prototype enabled by Muzicodes. - Martinez Avila, Juan Pablo (2016)
Commonly, music learners are required to practice with their instrument independently, requiring them to critically analyse their own performance. However, most novice musicians often lack the necessary auditory skills to make precise judgements of their performance, which may often lead to frustration and abandonment of the instrument. In these regards, Computer Assisted Musical Instrument Tutoring (CAMIT) systems have demonstrated having positive effects on the enhancement of self-analysis and motivation of learners, due to their remarkable use of audio signal processing, but primarily, their implementation of appealing interactive elements and multimedia contents which deliver the instructional materials and dynamics. Nevertheless, there are evident contrasting views on the appropriate balance and integration of the instructional, musical, and playful affordances often involved in these systems, as well as a lack of studies that assess how different arrangements of these affordances can result in different outcomes on the learning and engagement of users. In this dissertation project we offer a Human Computer Interaction perspective on analysing how different arrangements of these interactive elements can exert an effect on the perceived learning outcome of musical skills from a user standpoint. Thus, by using the Muzicodes system, which allows for strings of musical notes to be used as triggers for external media, a high-fidelity prototype of a CAMIT system was developed, presenting two different variations of juxtaposed interactive elements applied to an ear training task. Subsequently, user testing and semi-structured interviews were conducted with 10 intermediate musicians, in order to make a qualitative assessment of the advantages and disadvantages of each arrangement of interactive elements. Findings revealed a preference for cognitive-engaging challenges, which properly aligned the musical skills to be trained with the task to be solved. Based on these remarks we offer some design suggestions for similar CAMIT systems in the future.